HARAPAN SATUAN PENGAMANAN (SATPAM) TERHADAP PENDIDIKAN ANAKNYA - Syafdina, Intan; Ayub, Daeng; Arien, Wilasari (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Education is regarded as a crucial factor in improving quality of life and social mobility, thus becoming a top priority for parents, including those working as Security Guards (Satpam). This study aims to identify and analyze the level of expectations that security guards at PT Musim Mas, Pangkalan Lesung District, hold regarding their children’s education, with an emphasis on four indicators: goals, motivation, optimism, and resilience in facing challenges. The research employed a descriptive quantitative method with a population of 166 security guards and a sample of 118 respondents selected through simple random sampling. The research instrument consisted of a questionnaire that had been tested for validity and reliability, while the data were analyzed using descriptive statistics to measure the mean score tendencies of each indicator. The results showed that the expectations of the security guards were in the high category, with an overall mean score of 4.27. Among the indicators, motivation ranked the highest (4.68), while goals were the lowest (4.08). These findings indicate that despite economic constraints, security guards continue to prioritize their children’s education as an investment in the family’s future. This study underscores that parents’ motivation and optimism play a significant role in realizing better educational opportunities for their children.